Pengembangan Kompetensi Sumber Daya Manusia Berstandar Pariwisata Internasional untuk Peningkatan Kesejahteraan Masyarakat Kabupaten Badung - Sihombing, Urkanus (Research and Development Agency Ministry of Home Affairs, 2021)
This study aims to find a strategy for economic recovery through the development of human resource competencies with international tourism standards to improve people's welfare and realize the vision of the Regent and Deputy Regent of Badung in 2021-2024, namely Continuing the Happiness of the Badung Community through Development based on Tri Hita Karana. This study uses a qualitative method with a case study on the competency development program at the Agency for Personnel and Human Resources Development of the Badung Regency Government. This study finds the importance of planning and implementing human resource competency development managed by professional training institutions to produce reliable and competitive human resources and ready to meet the needs of the tourism business community in the Badung area and outside the region, including especially ten new tourist destinations that announced by the central government. For the management of human resource competency development to achieve optimal results, the learning management will utilize an online learning system and a mix of online with face-to-face/practice (blended learning). Commitment and innovative leadership from the Regent and Deputy Regent of Badung, combined with the mapping of competency development priorities of strategic value, are expected to immediately restore the economic conditions experienced by the people in Badung Regency.